On the primitive irreducible representations of finitely generated nilpotent groups - Tushev, A.V. (Reports of the National Academy of Sciences of Ukraine, 2021)
We develop some tecniques whish allow us to apply the methods of commutative algebra for studing the representations of nilpotent groups. Using these methods, in particular, we show that any irreducible representation of a finitely generated nilpotent group G over a finitely generated field of characteristic zero is induced from a primitive representation of some subgroup of G.